Political Action II, 1979-1981 - Jennings, M. Kent ([Verlag nicht ermittelbar], 1991)
This data collection focuses on conventional and unconventional forms of political participation and closely follows the format of the first Political Action study, POLITICAL ACTION: AN EIGHT NATION STUDY, 1973-1976 (ICPSR 7777). POLITICAL ACTION II consists of two parts: a second panel wave of reinterviews with respondents from the first Political Action surveys and a new cross-section sample. Topics covered include respondent's level of satisfaction with material standard of living, interest in politics, perception of privileged and under-privileged groups, opinions on various social and political issues, and ranking of important political goals. Additional variables address the performance of the present government, good and bad aspects of major left and major right parties, legitimacy of the present government and the political system in general, approval of protest behavior, participation in conventional and unconventional activities, voting behavior, attitudes toward young people, and political trust items. Background information provided for respondents includes age, sex, ethnic origin, education, religion, marital status, number of children, employment status, occupation, union membership, personal and family income, organizational memberships and activities, and father's and mother's education and political preferences.